2014
DOI: 10.4149/neo_2014_037
|View full text |Cite
|
Sign up to set email alerts
|

ZNF139 promotes tumor metastasis by increasing migration and invasion in human gastric cancer cells

Abstract: Zinc finger protein 139(ZNF139), a member of zinc finger protein family, is a transcription factor. Our previous research showed ZNF139 was overexpressed in gastric cancer cells. The purpose of present study is to explore impact and mechanism of ZNF139 on metastasis by regulating invasive ability of gastric cancer cells.Quantitative RT-PCR(QRT-PCR) and Western blot were applied for detection of ZNF139 expression in gastric cancer tissues, adjacent cancer tissues, metastatic lymph nodes, gastric cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…In gastric cell lines, it has also been shown to promote migration, invasion, and multidrug resistance [41,42]. Knockdown of ZKSCAN1 in GC cell lines leads to changes in expression of MMP2 , MMP9 , ICAM1 , and TIMP1 , impacting cell adhesion and matrix metalloprotease activities [42]. BCL-2 and other modulators of apoptosis are also among the ZKSCAN1 targets [41].…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cell lines, it has also been shown to promote migration, invasion, and multidrug resistance [41,42]. Knockdown of ZKSCAN1 in GC cell lines leads to changes in expression of MMP2 , MMP9 , ICAM1 , and TIMP1 , impacting cell adhesion and matrix metalloprotease activities [42]. BCL-2 and other modulators of apoptosis are also among the ZKSCAN1 targets [41].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (66) demonstrated that zinc finger protein 139 (ZNF139) regulated ANXA1 and ANXA5 expression, and promoted the LN metastasis of GC. ZNF139 is associated with multidrug resistance, and may promote GC invasion and metastasis (67,68).…”
Section: Alterations In Gene Expression In Metastatic Lnsmentioning
confidence: 99%
“…van Dekken et al [13] discovered that the expression of ZNF139 was increased in adenocarcinoma of esophago–gastric junction. Also, ZNF139 can promote the invasion and progression of GC cells [15]. After using RNAi technique to suppress the expression of ZNF139, we found that gastric cell line MKN28 became more sensitive to chemotherapeutic drugs, and related drug-resistance genes varied [16].…”
Section: Discussionmentioning
confidence: 99%
“…van Dekken et al [13] discovered that the expression of ZNF139 increased in cancer tissues of the gastro–esophageal junction and may be related to cancer growth and development, and the same research team also revealed that ZNF139 has participated in the process of gastric cells differentiation [14], promoting invasion and development of GC cells [15]. Furthermore, the increased expression of ZNF139 is also closely related to GC MDR [16].…”
Section: Introductionmentioning
confidence: 99%